1999
DOI: 10.1038/sj.jhh.1000925
|View full text |Cite
|
Sign up to set email alerts
|

ABPM comparison of the antihypertensive profiles of the selective angiotensin II receptor antagonists telmisartan and losartan in patients with mild-to-moderate hypertension

Abstract: The antihypertensive efficacy and tolerability profiles of the selective AT1 receptor antagonists telmisartan and losartan were compared with placebo in a 6-week, multinational, multicentre, randomised, double-blind, double-dummy, parallel-group study of 223 patients with mild-to-moderate hypertension, defined as clinic diastolic blood pressure (DBP) >/=95 and /=140 and /=85 mm Hg. After a 4-week single-blind placebo run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
9

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(104 citation statements)
references
References 23 publications
2
93
0
9
Order By: Relevance
“…Telmisartan administered in single daily doses of 40 and 80 mg was superior to placebo, losartan 50 mg/day, valsartan 80 mg/day and amlodipine 5 mg/day in lowering the systolic blood pressure (SBP) and diastolic blood pressure (DBP) and preventing their early morning rise as illustrated in Figure 6a and b for the SBP and DBP, respectively. 44,45 In another double-blind, 46 In other short-term studies, telmisartan was as effective or better than atenolol, 47 enalapril 48 and lisinopril. 49 Telmisartan has also been combined with a low-dose diuretic for better blood pressure control.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 91%
“…Telmisartan administered in single daily doses of 40 and 80 mg was superior to placebo, losartan 50 mg/day, valsartan 80 mg/day and amlodipine 5 mg/day in lowering the systolic blood pressure (SBP) and diastolic blood pressure (DBP) and preventing their early morning rise as illustrated in Figure 6a and b for the SBP and DBP, respectively. 44,45 In another double-blind, 46 In other short-term studies, telmisartan was as effective or better than atenolol, 47 enalapril 48 and lisinopril. 49 Telmisartan has also been combined with a low-dose diuretic for better blood pressure control.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 91%
“…Significant reductions in both systolic and diastolic blood pressure were seen 48 h after dosing with candesartan, whereas in losartantreated patients blood pressures were not significantly different from baseline values at this time ( Figure 6). Indeed, the effect on blood pressure seen 48 h after dosing with candesartan was comparable with that seen with losartan after 24 h. Similar results were obtained in a second study with ambulatory blood pressure monitoring, in which the antihypertensive effect over 36 h of candesartan cilexetil, 8 mg, was significantly greater than that of losartan, 50 mg. 31 Other studies have shown that irbesartan, 150 mg, and telmisartan, 40-80 mg, appear to have greater effects on ambulatory blood pressure than valsartan, 80 mg, or losartan, 50 mg. [32][33][34][35][36] The available studies thus indicate that the therapeutic effect of candesartan is maintained even if a dose is delayed or missed, and hence candesartan offers extended therapeutic coverage. The potential importance of this extended therapeutic coverage is underlined by studies of adherence with antihypertensive medication.…”
Section: Duration Of Antihypertensive Efficacymentioning
confidence: 99%
“…[10][11][12][13][14][15] Hydrochlorothiazide (HCTZ) is a benzothiadiazide diuretic; these agents lower blood pressure through alteration of the sodium balance. HCTZ also augments the therapeutic response to some other classes of antihypertensive agents.…”
Section: Introductionmentioning
confidence: 99%